A model of an integration system for operations and cost data designed to control logistics processes in agricultural enterprises - Karol Wajszczuk; Jacek Wawrzynowicz; Bogusław Śliwczyński (Contemporary Economics, 2011)
The paper presents a model of an integration system for operations and cost data designed for the needs of process controlling in agricultural enterprises, with special emphasis on logistics processes. The proposed model constituted the basis for the development of an IT tool to be used in the identification and analysis of logistics costs in agricultural enterprises in terms of the process based approach. As a result of research and programming efforts a model was developed, which made it possible in agricultural enterprises to determine the type-based relationship of cost dynamics and structure with realized actions, operating processes (including logistics processes) and products, as well as the relationship of these costs with used resources, maintained stocks, applied materials and work methods. Moreover, this model facilitates cost allocation to products and processes as well as cost centers and points, and makes it possible to determine multidimensional dependencies of the result (divided into individual products) on incurred costs.
Keywords: M21; M41; Q10; 330; operating costs; logistics costs; management accounting; process analysis; controlling; agricultural enterprises